2014
DOI: 10.3892/etm.2014.1905
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV inhibits platelet-derived growth factor-BB-stimulated proliferation and migration of vascular smooth muscle cells via the inhibition of p38 MAPK signaling

Abstract: Astragaloside IV (AS-IV), the major active component extracted from Astragalus membranaceus, has been demonstrated to exhibit protective effects on the cardiovascular, immune, digestive and nervous systems; thus, has been widely used in traditional Chinese medicine. Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) is closely associated with the initiation and progression of cardiovascular diseases, including atherosclerosis and restenosis. However, the effects of AS-IV on VSMCs rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
4
24
0
Order By: Relevance
“…Such a process is the early stage of atherosclerosis, while VSMC migration and the subsequent formation of foam cells is the later process for the formation of atherosclerotic plaque. Phenotypic transformation is considered as a critical process for VSMC proliferation and migration [22]. In this study, the phenotypic transformation and migration ability of Ox-LDL-treated VSMCs was found to be higher than that in the blank control group, which was in agreement with the results from other studies.…”
Section: Discussionsupporting
confidence: 83%
“…Such a process is the early stage of atherosclerosis, while VSMC migration and the subsequent formation of foam cells is the later process for the formation of atherosclerotic plaque. Phenotypic transformation is considered as a critical process for VSMC proliferation and migration [22]. In this study, the phenotypic transformation and migration ability of Ox-LDL-treated VSMCs was found to be higher than that in the blank control group, which was in agreement with the results from other studies.…”
Section: Discussionsupporting
confidence: 83%
“…Herein, it was reported that formononetin suppressed PDGF-BB-stimulated VSMCs proliferation. Furthermore, the results indicate that PDGF-BB could induce VSMCs to dedifferentiate into a proliferative phenotype, as suggested by the downregulation of SMA, smoothelin and desmin, which is consistent with previous studies (16,24). However, treatment with formononetin attenuated the PDGF-BB-induced downregulation of SMA, smoothelin and desmin, indicating that formononetin inhibited the PDGF-BB-induced phenotype change in VSMCs.…”
Section: Discussionsupporting
confidence: 80%
“…Cell cycle-related proteins, including CDK2, CDK4, cyclin D1 and cyclin E, are crucially involved in the regulation of cell cycle progression, as well as cell proliferation (16). It has been reported that formononetin has effects on the expression of cell cycle-related proteins (8).…”
Section: Formononetin Inhibited the Pdgf-bb-induced Expression Of Celmentioning
confidence: 99%
“…p38 MAPK signaling pathway is significantly inhibited by PDGF-induced proliferation in smooth muscle cells. For example, astragaloside IV inhibits PDGF-stimulated proliferation by inhibiting p38 MAPK in human vascular smooth muscle cells [16]. p38 MAPK activation is also required for the esculetin-induced inhibition of vascular smooth muscle cell proliferation [17].…”
Section: Introductionmentioning
confidence: 99%